Making an impact? The relevance of information on aid effectiveness for charitable giving. A laboratory experiment - Laura Metzger; Isabel Günther (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2015)
A considerable and increasing share of foreign aid stems from private donations. Hence, individual donors can increase social welfare in developing countries by directing their funds to the most effective NGOs. Surprisingly few studies have analyzed whether private donors care about aid effectiveness when they donate to an international charity. In a laboratory experiment, we investigate if private donors seek information about the exact impact of their donation to an international NGO before they donate. Furthermore, we investigate how relevant private donors find information about aid impact compared to information about administrative costs, and the recipient type who benefits from a donation. First, we find that a relatively small share of individuals makes a well-informed donation decision. Second, the demand for information about aid impact is lowest, and it is highest for information about the recipient type. Third, exact information about aid impact did not lead to a significant change in average donation levels, while information about the exact recipient type and administrative costs led to a significant change in donation levels. In the recipient type group, informed participants donated significantly more than uninformed participants because they "rewarded" the preferred recipient with higher-thanaverage transfers. In the administration costs group, informed participants donated significantly less than uninformed participants because they used the information to "punish" NGOs with high administration costs.
Keywords: D64; L31; O12; 330; Charitable giving; aid impact; aid effectiveness; fairness; social preferences